Installation and experiments on 14 Kw gasifier system - Shukla S.K.; Rahul Sharma N.V.; Kumar S.; Kumar A. (My University, 2025)
In the present energy crisis scenario, focus of the scientist struggle is to produce sustainable, renewable and continuous form of energy. In this quest, the response of energy production technique using gasification has reproduced positive results. In this project we have focused to substitute diesel consumption using producer gas in a dual fuel power generator. It involves the installation of one 14 kWe biomass gasifier system with dual fuel engine and generator in the IIT (BHU) campus. The performance of the system is studied under actual varying load by connecting it to the various loads and using woody biomass. Then, the performance data of the system are obtained using a combination of locally available fuels like rice husk, nut shell, cotton stock and eupatorium. Based on the data obtained, modifications required to improve the performance will be suggested. The performance study of the modified system may be taken up as a future work. Based on few simple calculations it can be shown that, the cost of power generation using a woody biomass gaisfier system is around Rs. 3.5 per unit. This is much cheaper when compared to the cost power generation using diesel. However, the technology needs refinement in the areas of fuel quality, retrofitting performance data for locally available fuels etc. The proposed project is expected to yield fruitful results in this area. This will in turn make the technology and technical expertise available for commercial applications in this area. © 2015 IEEE.